Formation of compact galaxies in the Extreme-Horizon simulation: letter to the editor - Chabanier, Solène; Bournaud, F.; Dubois, Y.; Codis, S.; Chapon, D.; Elbaz, D.; Pichon, C.; Bressand, O.; Devriendt, J.; Gavazzi, R.; Kraljic, K.; Kimm, T.; et al. (Astronomy and astrophysics, 2020)
We present the Extreme-Horizon (EH) cosmological simulation, which models galaxy formation with stellar and active galactic nuclei (AGN) feedback and uses a very high resolution in the intergalactic and circumgalactic medium. Its high resolution in low-density regions results in smaller-size massive galaxies at a redshift of z = 2, which is in better agreement with observations compared to other simulations. We achieve this result thanks to the improved modeling of cold gas flows accreting onto galaxies. In addition, the EH simulation forms a population of particularly compact galaxies with stellar masses of 1010−11 M⊙ that are reminiscent of observed ultracompact galaxies at z ≃ 2. These objects form primarily through repeated major mergers of low-mass progenitors and independently of baryonic feedback mechanisms. This formation process can be missed in simulations with insufficient resolution in low-density intergalactic regions.